Modal analysis of electromagnetic actuator for non-contact modal testing - Mohamad Asyraf, Ahmad Bustamang (2013)
Low surface finish, low accuracy and reduction in tool life were happening towards the machining product and cutting tools during high speedmachining (HSM) process. The defects were happening because of chatter effect or resonance of the whole machine system. A study was conducted to study and optimizing between tool-life and machining speed operation for controlling these chatter effect by using an electromagnetic actuator (EMA) anon-contacting excitation force. The objective of this project is to determine the modal analysis of electromagnetic actuator for non-contact modal testing. The method use for determining modal analysis of electromagnetic actuator by modal testing was by electromagnetic shaker. The modal analysis of electromagnetic actuator was determined by comparison result of computational and experimental modal analysis methods. The electromagnetic actuator was analysed in two types that were structured with and without electromagnetic core for each of modal analysis methods. ANSYS 14.0 was used as the finite element analysis (FEA) software for generating modal analysis of the structure and ME‟Scope software used for determining the modal analysis based on the experimental method. The result of these modal analyses was supported by result of operational deflection shape (ODS) for each type of assembling the structure. The result of modal analysis of electromagnetic actuator was determined based on the similarity data collected between computational and experimental methods. The operational deflection shape determines the deflection of the structure under certain operation condition. Based on modal analysis and operational deflection shape, the structure of electromagnetic actuator can be used for the experiment with high frequency excitation.